2016
DOI: 10.1063/1.4962743
|View full text |Cite
|
Sign up to set email alerts
|

The diffusion and conduction of lithium in poly(ethylene oxide)-based sulfonate ionomers

Abstract: Pulsed field gradient nuclear magnetic resonance spectroscopy and dielectric relaxation spectroscopy have been utilized to investigate lithium dynamics within poly(ethylene oxide) (PEO)-based lithium sulfonate ionomers of varying ion content. The ion content is set by the fraction of sulfonated phthalates and the molecular weight of the PEO spacer, both of which can be varied independently. The molecular level dynamics of the ionomers are dominated by either Vogel-Fulcher-Tammann or Arrhenius behavior dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…c) High shear modulus of the electrolyte, where elastic-plastic deformation of both lithium and electrolyte occurs. Lithium Poisson's ratio --0.42 [23] Yield strength of lithium 0.4 [47,49] Hardening modulus of lithium 1.9 [47,49] Hardening exponent of lithium --0.4 [47,49] PEO Yield strength of PEO polymer 0.77 [12,48] Hardening modulus of PEO polymer 3.5 [12] Hardening exponent of lithium --0.4 [12] Partial molar volume of lithium 1.3x10 -5 [23] Partial molar volume of electrolyte salt 1.674x10 -4 [23] Lithium diffusion coefficient 1x10 -12 [65,66] Lithium transference number --0.3 [23,35] Thermodynamic factor --1. [31,55] Amplitude 400.0 [31,55] Anodic and cathodic reaction rate constants 9.832x10 -6 [23,35] Anodic and cathodic transfer coefficients --0.5 [23,35] Domain length [23] Universal which concentration and potential distributions were calculated.…”
mentioning
confidence: 99%
“…c) High shear modulus of the electrolyte, where elastic-plastic deformation of both lithium and electrolyte occurs. Lithium Poisson's ratio --0.42 [23] Yield strength of lithium 0.4 [47,49] Hardening modulus of lithium 1.9 [47,49] Hardening exponent of lithium --0.4 [47,49] PEO Yield strength of PEO polymer 0.77 [12,48] Hardening modulus of PEO polymer 3.5 [12] Hardening exponent of lithium --0.4 [12] Partial molar volume of lithium 1.3x10 -5 [23] Partial molar volume of electrolyte salt 1.674x10 -4 [23] Lithium diffusion coefficient 1x10 -12 [65,66] Lithium transference number --0.3 [23,35] Thermodynamic factor --1. [31,55] Amplitude 400.0 [31,55] Anodic and cathodic reaction rate constants 9.832x10 -6 [23,35] Anodic and cathodic transfer coefficients --0.5 [23,35] Domain length [23] Universal which concentration and potential distributions were calculated.…”
mentioning
confidence: 99%
“…Significant enhancements of conductivity relative to Nernst-Einstein predictions have been observed 154 , but the intrinsically slow dynamics of polymeric materials has made it difficult to obtain materials with values comparable to small molecule fluids. Recently, it has been suggested that lowering the dielectric constant of the polymer matrix 155 should greatly improve the situation and other strategies are actively being pursued.…”
Section: Discussionmentioning
confidence: 99%
“…Using the unpaired cation fraction of −23% for Li + as determined from Raman spectroscopy and a measured density of 1.28 g/mL, we estimate the Li + diffusivity in PEG 31 DA-x-STFSILi as 6 × 10 −24 cm 2 /s at 20 • C. Na + and K + diffusivities at 20 • C are estimated as 5 × 10 −25 and 3 × 10 −25 cm 2 /s, respectively, for PEG 31 DA-x-STFSINa and PEG 31 DA-x-STFSIK. The Li + diffusivity value estimated here should in the future be compared to the 7 Li self-diffusion coefficient as measured via pulse-field gradient nuclear magnetic resonance spectroscopy (PFG-NMR) [55]. While several other works have used Raman spectroscopy to estimate the degree of TFSI anion coordination in electrolytes such as ionic liquids, we believe that this is the first effort to apply this approach to single-ion conducting polymers with tethered STFSI anions.…”
Section: Introductionmentioning
confidence: 92%